2017
DOI: 10.1007/s00247-017-3996-5
|View full text |Cite
|
Sign up to set email alerts
|

Female gonadal shielding with automatic exposure control increases radiation risks

Abstract: Female gonadal shielding combined with AEC during pelvic radiography increases absorbed dose to organs with greater radiation sensitivity and to unshielded ovaries. Difficulty in proper use of gonadal shields has been well described, and use of female gonadal shielding may be inadvisable given the risks of increasing radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 26 publications
1
23
0
2
Order By: Relevance
“…Several studies pointed to inadequate placement of gonad shields, the concomitant loss of diagnostic information and the low doses currently involved, but were cautious with their advice. A few suggest reconsidering or ending the practice in female children [6][7][8][9][11][12][13], in male children [7,9,12] or in all [3,10]. Marsh and Silosky are more outspoken when referring to the officially still endorsed practice of gonad shielding as "…the folly of its continued use…" [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies pointed to inadequate placement of gonad shields, the concomitant loss of diagnostic information and the low doses currently involved, but were cautious with their advice. A few suggest reconsidering or ending the practice in female children [6][7][8][9][11][12][13], in male children [7,9,12] or in all [3,10]. Marsh and Silosky are more outspoken when referring to the officially still endorsed practice of gonad shielding as "…the folly of its continued use…" [4].…”
Section: Discussionmentioning
confidence: 99%
“…The ICRP (2013) [1] and IAEA (2018) [2] endorse this practice, whereas others, such as the Dutch guidelines [3], Marsh and Silosky [4] and the AAPM [5], no longer recommend it. Other authors dismiss gonad shielding partly or express their doubts about existing benefits [6][7][8][9][10][11][12][13]. This debate should ideally be decided by a quantitative analysis based on proper knowledge of radiation risks, reduction in hereditary risk by gonad shielding and the increase in risk caused by negative side-effects of shielding.…”
Section: Introductionmentioning
confidence: 99%
“…Kaplan et al [26] investigated on whether a gonadal shielding may affect the automatic exposure control (AEC) response. They showed that female gonadal shielding combined with AEC during pelvic radiography increases absorbed dose to organs with greater radiation sensitivity and to unshielded ovaries.…”
Section: Gonadal Shieldingmentioning
confidence: 99%
“…Often, efforts to reduce patient dose using gonadal shields actually increase dose because inadequate coverage of the gonads or the obscuration of critical anatomy may result in a repeated x ray. Even if the shield is correctly placed on the anatomy, the automatic exposure control phototiming cells may be covered, leading to increased radiation output of 63% for pediatrics to 147% for adults …”
Section: For the Proposition: Sarah Mckenney Phdmentioning
confidence: 99%
“…Additionally, shielding does not protect the patient from internally scattered radiation. Depending on the patient size, scattered radiation can substantially contribute of the radiation dose delivered to the ovaries . While we strive for equality in healthcare, gonadal shielding is nothing more than good intentions for the female population.…”
Section: For the Proposition: Sarah Mckenney Phdmentioning
confidence: 99%